Analisa Terbentuknya Negatif Opini Publik Undang-Undang Cipta Kerja di Provinsi Kalimantan Selatan - Irwansyah; Ahmad Alvin Ferdian; Zulfiana Enni Rizqa; Muzahid Akbar Hayat (Jurnal Kebijakan Pembangunan, 2021)
The Job Creation Act which was ratified on 5 October 2020 was met with the agitation of rejection in the form of demonstrations in almost all parts of Indonesia. There are many misunderstandings in the interpretation of this law, one of which is the assumption that the law will harm workers and society. This study aims to identify the causes of negative public opinion on the Job Creation Act, what forms of socialization are carried out by the government, and how the public gets information about the law. This research uses a qualitative approach. The data was taken through a questionnaire distributed to 22 respondents who were randomly selected from the Job Creation Act demonstrators in November 2020 in front of the DPRD Building of South Kalimantan Province. The results showed that respondent’s negative opinion on the Job Creation Act was caused by a lack of knowledge about the contents of the law and the lack of government socialization to the public. The strategy that can be taken by the government to create positive public opinion is to involve community groups, students, public figures, religious leaders, community leaders, and influencers as communicants or messengers in the socialization of the Job Creation Act.